(untitled)
This research aims to study and prepare a highly effective catalyst (Gama- alumina) because of its importance in the industry; From raw materials available cheapThe price is somewhat, as the remnants or residues of aluminum factories were taken as raw materialsTo prepare the active phase of alumina, which is 81203 7. The research also included a study of the best temperatures to obtainAlumina phase where the results showed that the best temperature was between(